International Transport Management - Aykor, A. Mert (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
This book analyzes the latest trends and technologies in the global transportation industry of the 21st century, introducing sharp and high-tech transportation logistics tools. The book provides a comprehensive overview of global transportation logistics, including valuable information provided by relevant federations and organizations representing the transportation sector. Additionally, it presents the latest version of Incoterms 2020 with all its new features and characteristics. This study serves as an indispensable resource for all parties involved in multinational transportation logistics. Furthermore, the author welcomes constructive contributions from readers in the form of opinions and suggestions regarding this work.